A misdiagnosis of mesh extrusion treated as a psychiatric female pelvic pain. Issue 1 (February 2022) - Illiano, Ester; Mancini, Vito; Trama, Francesco; Maghlhàes Vasconcelos, Larissa; Carrieri, Giuseppe; Costantini, Elisabetta
Introduction: Complications due to prosthetic surgery with mesh implantation may be misunderstood due to the insidious clinical presentation and inexperience of many surgeons if not adequately trained for the purpose. Case report: A 45-year-old female underwent a trans obturator tape procedure to correct severe stress urinary incontinence 3 months after surgery she developed urethral pain. The sling was partially removed, but the pain persisted. No residue sling was visualized by cystoscopies after surgery, and the pain was attributed to a psychiatric problem. She was treated with opioids, pregabalin without improvement of pain, until an extrusion of the sling into the urethra has been diagnosed by a careful urethrocystoscopy. Conclusion: It has been treated in our department by the removal of the residual sling, plus urethroplasty. The patient was followed up at 6 months with resolution of the painful symptoms.